Colonoscopic Clipping as a Treatment for Appendiceal Bleeding (Gut and Liver, 2010)
Bleeding from the appendix has been reported very rarely in patients with lower-gastrointestinal-tract bleeding. In general, after a colonoscopic diagnosis of appendiceal bleeding, laparoscopic or surgical appendectomy would be recommended. Two patients with continuous bleeding from the appendix were treated with partial occlusion of the appendiceal orifice by colonoscopic clipping. In neither case was there evidence of further active bleeding over the following 12 months. This is the first report of such a treatment in the English literature. (Gut Liver 2010;4:411-414)